The wasp genus Olixon Cameron in Madagascar: first record and description of two new species (Hymenoptera: Rhopalosomatidae) - Lohrmann, Volker; Ohl, Michael (Zootaxa, 2007)
Two new species, Olixon toliaraensis sp. nov. and Olixon martini sp. nov. (Hymenoptera: Rhopalosomatidae) are described from Madagascar. They represent the first record of this genus from this island. The two species are morphologically similar, but Olixon toliaraensis sp. nov. is mainly characterized by an indentation of the apicolateral carina of the head and a vertex with a weak medial impression. Olixon martini sp. nov. lacks these characters. Photos of the new species, drawings of the diagnostic characters, a distribution map, and an updated key to the Olixon of the world are provided.